The long-run determinants of fertility: One century of demographic change 1900 - 1999 - Dierk Herzer; Holger Strulik; Sebastian Vollmer (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2010)
We examine the long-run relationship between fertility, mortality, and income using panel cointegration techniques and the available data for the last century. Our main result is that mortality changes and growth of income per capita account for a major part of the fertility change characterizing the demographic transition. The change of mortality alone, however, is insufficient to explain the secular decline of population growth. For that interaction of mortality and income growth is needed. These results are robust against alternative estimation methods, potential outliers, sample selection, different measures of mortality, and the sample period. In addition, our causality tests suggest that fertility is both endogenous and exogenous. In particular, we find that an increase of fertility reduces growth of income per capita.
Keywords: J1; J13; C23; 330; Fertility; mortality; economic development; panel cointegration; Demographischer Übergang; Entwicklung; Sterblichkeit; Einkommen; Wirtschaftswachstum; Schätzung; Welt